A eficácia das audiências de custódia como mecanismo de redução do encarceramento provisório: um estudo de caso sobre a atuação da Central de Inquéritos de São Luís/MA à luz da Criminologia Crítica. - GAMBA, Cristian de Oliveira (2021)
The present study aims to evaluate the efficacy of custody hearings as a mechanism to reduce pre-trial incarceration levels in the city of São Luís/MA since it was one of the main goals of its implementation in the national territory, according to the judgment of ADPF n° 347 of 2015 by the Supreme Federal Court.It is a qualitative-quantitative research, of the evaluative type, whose method of approach is the inductive. The procedural method is perfected through the case study about the performance of the São Luís/MA Inquiry Center, the agency responsible for carrying custody hearings at the municipal level, encompassing the time lag between the years 2014 to 2019. Methodological procedures used to make the case study feasible were bibliographic research as well as documentary research, the latter focusing on two fronts: the compilation and organization of official data relevant to provisional incarceration in the state and municipal areas, as well as those related to the performance of the Inquiry Center, and the analysis of the grounds for judicial decisions issued by the agency. Finally, it was concluded that custody hearings, despite its undeniable guarantist character, have not directly influence to decrease the quantitative of pre-trial detainees at a municipal level. This is a result, primarily of the massive use of precautionary custody as a containment instrument for supposedly dangerous individuals, subverting its precautionary nature and utilizing it as a mechanism to anticipate imprisonment.